SWOT Analysis in Optimizing Financial Technology in Islamic Cooperative to Increase Islamic Financial Inclusion - Salama, Sri Cahyaning Umi; Millatina, Afifah Nur (UPT Penerbitan Universitas Jember, 2025)
Financial technology has great potential to enhance financial accessibility, particularly for members of Baitul Maal wa Tamwil (BMT) or Islamic cooperatives. However, the adoption of micro-fintech (fintech in microfinance institutions) still faces various challenges, such as limited adoption of technology, regulations, and competition with conventional fintech. This study aims to analyze the strategy of optimizing financial technology in Islamic microfinance institutions to increase Islamic financial inclusion in Indonesia using the SWOT analysis approach. This study is a qualitative study with data collection techniques through observation and literature studies. Based on the results of the SWOT analysis, the strategy for optimizing micro-fintech can be carried out by developing a more inclusive digital platform, increasing education and digital literacy for members, and strengthening cooperation with various parties, including the government and Islamic financial institutions. With the right approach, micro-fintech implementation in BMT can be more effective in increasing islamic financial inclusion in Indonesia.